2000
DOI: 10.1128/iai.68.4.2161-2166.2000
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium difficile Recombinant Toxin A Repeating Units as a Carrier Protein for Conjugate Vaccines: Studies of Pneumococcal Type 14, Escherichia coli K1, and Shigella flexneri Type 2a Polysaccharides in Mice

Abstract: Unlike the native protein, a nontoxic peptide (repeating unit of the native toxin designated rARU) from Clostridium difficile toxin A (CDTA) afforded an antigen that could be bound covalently to the surface polysaccharides of pneumococcus type 14, Shigella flexneri type 2a, and Escherichia coli K1. The yields of these polysaccharide-protein conjugates were significantly increased by prior treatment of rARU with succinic anhydride. Conjugates, prepared with rARU or succinylated (rARUsucc), were administered to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 45 publications
1
19
0
Order By: Relevance
“…Purified His-tagged rARU was kindly provided by David M. Lyerly and Limin Zheng (Techlab, Inc., Blacksburg, VA) (31), and His-tagged rGTFC was purified as described previously (50). These two recombinant proteins were purified to homogeneity by affinity chromatography, and the protein purity was determined by silver staining of sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) gels.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Purified His-tagged rARU was kindly provided by David M. Lyerly and Limin Zheng (Techlab, Inc., Blacksburg, VA) (31), and His-tagged rGTFC was purified as described previously (50). These two recombinant proteins were purified to homogeneity by affinity chromatography, and the protein purity was determined by silver staining of sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) gels.…”
Section: Methodsmentioning
confidence: 99%
“…Unlike for other repeats, little is known about the biological functions of CROPs. Besides carbohydrate-binding activity, the TcdA CRD has an immune modulating effect when used as an adjuvant or carrier protein for mucosal immunization (4,31). Nevertheless, conflicting results have been ob-tained from in vitro studies of the biological activity of the CRD of TcdA alone in different cell culture systems: activation signals were detected in epithelial cells (33), but no activation was observed for monocytes (16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The control group, in which sequence as the antigens. Previous studies have mainly identified the C-terminal domain for both toxin A and toxin B, 16 toxin A C-terminal repeating units 17,18 or even one or multiple copies of antigenic peptides in this region as the main antigenic regions that can elicit protective antibody responses. 19,20 In addition to protein-or subunit-based vaccines, novel bacterial vectors have also been used to successfully deliver antigenic domains to elicit protective immunity.…”
Section: Introductionmentioning
confidence: 99%
“…We improved the immunogenicity of Shigella conjugates as assayed in mice by introduction of another carrier protein, Corynebacterium diphtheriae CRM9 (a genetically derived nontoxic mutant of C. diphtheriae) (34) and by succinylation of the proteins prior to binding to the polysaccharide (27,42,43). Succinylation of a mutant Clostridium difficile toxin increased its solubility and its effectiveness for conjugates (43).…”
mentioning
confidence: 99%